Imposter phenomenon and basic psychological needs predict self-evaluations of knowledge and ability relative to others - Biblekaj, Viktoria; Kahlbaugh, Patricia (International Journal of Personality Psychology, 2026)
Imposter Phenomenon (IP) is a set of psychological experiences characterized by self-doubt, attributing success to external causes, and a constant fear of being perceived as a phony (Clance & Imes, 1978), which may be suggestive of dissatisfaction with basic psychological needs of competence, autonomy, and relatedness. Amazon Mechanical Turk (MTurk) workers (N = 325, 61% men, 39% women) ranked their self-identified knowledge and abilities relative to others, completed the Clance Imposter Phenomenon Scale (CIPS) assessing IP, and the Balanced Measure of Psychological Needs (BMPN) assessing competence, autonomy, and relatedness. We hypothesized that IP and dissatisfaction in basic psychological needs would predict underestimation of knowledge and abilities relative to those of other people. However, we found imposter phenomenon and basic psychological needs predicted positive self-evaluations. Inflated self-evaluations may be strategically used to defend against IP feelings and against a sense of “ill-being” associated with thwarted psychological needs. Thus, a positive, confident presentation may be compensatory or defensive in nature. Future research could explore specific defense mechanisms that may mediate this positive self-evaluation of knowledge and ability relative to others as well as the role of styles of perfectionism.
Keywords: Basic needs; Feeling; Need theory; Phenomenon; Scale (ratio); Set (abstract data type); dept.psy

Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (Zenodo (CERN European Organization for Nuclear Research), 2026)
(1) Understanding the thermal sensitivity of reproductive interactions is crucial given global warming. Previous studies have almost exclusively focused on interactions before mating, even though important interactions between the sexes also occur after mating (e.g., gamete interactions), which are likely affected by temperature. (2) Thus, it remains unknown how temperature affects the influence of female reproductive fluid on sperm performance, thereby altering female control over fertilization (cryptic female choice). This gap limits our understanding of how sexual selection changes with seasonal temperature fluctuations and temperatures outside the range of historical norms. (3) We tested how temperatures relevant to current conditions and climate change projections influence the mechanisms underlying cryptic female choice in a marine fish, Symphodus ocellatus. Under typical thermal conditions, female reproductive fluid enhances sperm velocity and biases fertilization dynamics to favor preferred, dominant males over sneaker males. (4) We find that warmer temperatures decrease female influence on sperm velocity, especially for dominant males. This results in dominant males having slower sperm than sneaker males at warmer temperatures, reducing the expected paternity of preferred, dominant males. (5) Our results highlight that considering the thermal sensitivity of female-male interactions that occur after mating will be essential for understanding how seasonal variation and climate change can influence fertility, reproduction, and sexual selection.
Keywords: Climate change; Gamete; Mate choice; Mating; Mating system; Operational sex ratio; Sexual selection; Sperm; dept.psy

Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (2026)
(1) Understanding the thermal sensitivity of reproductive interactions is crucial given global warming. Previous studies have almost exclusively focused on interactions before mating, even though important interactions between the sexes also occur after mating (e.g., gamete interactions), which are likely affected by temperature. (2) Thus, it remains unknown how temperature affects the influence of female reproductive fluid on sperm performance, thereby altering female control over fertilization (cryptic female choice). This gap limits our understanding of how sexual selection changes with seasonal temperature fluctuations and temperatures outside the range of historical norms. (3) We tested how temperatures relevant to current conditions and climate change projections influence the mechanisms underlying cryptic female choice in a marine fish, Symphodus ocellatus. Under typical thermal conditions, female reproductive fluid enhances sperm velocity and biases fertilization dynamics to favor preferred, dominant males over sneaker males. (4) We find that warmer temperatures decrease female influence on sperm velocity, especially for dominant males. This results in dominant males having slower sperm than sneaker males at warmer temperatures, reducing the expected paternity of preferred, dominant males. (5) Our results highlight that considering the thermal sensitivity of female-male interactions that occur after mating will be essential for understanding how seasonal variation and climate change can influence fertility, reproduction, and sexual selection.
Keywords: Climate change; Gamete; Mate choice; Mating; Mating system; Operational sex ratio; Sexual selection; Sperm; dept.psy

Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (bioRxiv (Cold Spring Harbor Laboratory), 2025)
Abstract Reproduction is often more thermally sensitive than survival. Thus, understanding the thermal sensitivity of reproductive interactions is crucial given global warming. However, it is unknown how temperature influences female control over fertilization after mating ( i.e., cryptic female choice). We tested how temperatures relevant to current conditions and climate change projections influence cryptic female choice in a marine fish, Symphodus ocellatus . Under typical conditions, females bias fertilization dynamics to favor dominant males. We find that warmer temperatures decrease female influence on sperm velocity and reduce the expected paternity of dominant males. Our results demonstrate that temperatures relevant to climate change can shift the balance between mate choice and male-male competition. Thus, climate change may influence sexual selection, leading to evolutionary changes in reproductive traits.
Keywords: Geology; Oceanography; dept.psy

Role of an Intermediary Organization and State Government Partnership to Advance Practice and Policy in Children’s Behavioral Health - Lang, Jason; Randall, Kellie; Kelly, A.; Bracey, Jeana; Bridges-Hightower, Jenny; Newkirk, Katie; Lu, Jack; Gregory, Francis; Duran, Tracy; Geib, Catherine; Bozak, Stephanie; Mackey, Jocelyn; et al. (Prevention Science, 2026)
Keywords: Behavioral health; Bridge (graph theory); Diversity (politics); General partnership; Government (linguistics); Intermediary organization; Partnership; Plan (archaeology); Policy; Public policy; Research; State (computer science); System development; Workforce; Workforce development; dept.psy

Actigraphy-based sleep outcomes in substance use disorders: A systematic review and meta-analysis - Naveda, Alisson; Oliva, Henrique; Pulido-Saavedra, Alejandra; Ghadimi, Delaram; Moore, James; Morgan, Peter; Potenza, Marc; Angarita, Gustavo (Sleep Medicine Reviews, 2026)
Keywords: MEDLINE; Polysomnography; Sleep (system call); Substance use; Systematic review; dept.psy

Thinking differently: neurodivergent traits and responses to thought experiments in philosophers and the general population - McKee, Paul; Boulhadi, Khaoula; Weymouth, Helena; Nadelhoffer, Thomas (Philosophical Psychology, 2026)
Philosophers have long speculated that individual differences in temperament influence philosophical thinking, yet empirical research has rarely explored the role of neurodivergent traits in this domain. In this large online study (N = 1,254), we investigated whether participants with training in philosophy differ from the general population when it comes to six psychological traits–autism, ADHD, aphantasia, anendophasia, anauralia, and representational manipulation–and also whether these traits correlate with responses to two widely studied philosophical thought experiments: the “trolley problem” and the “rollback deterministic universe.” Compared to the general population, participants with training in philosophy had higher scores on measures of ADHD, internal verbalization, and representational manipulation, but lower scores on measures of visual imagery. These cognitive traits were also correlated with participants’ moral and metaphysical judgments (independent of their level of philosophical training)–e.g. participants who scored higher in visualization were less likely to judge that hitting the switch in the trolley problem is permissible but not obligatory, and also less likely to attribute free will and moral responsibility to agents in the rollback universe. Finally, we employed machine learning to develop predictive models that classify a randomly selected participant as either a philosopher or a non-philosopher. Models trained solely on responses to measures for neurodivergent traits achieved better performance than models trained solely on responses to philosophical thought experiments. This suggests that stable, trait-level neurodivergent characteristics may be more diagnostic of philosophical interest, aptitude, or training than judgments philosophers make on domain-relevant problems. © 2026 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Neurodiversity; dept.psy; experimental philosophy; free will beliefs; general population; moral judgment; philosophers

Investigating the analytical robustness of the social and behavioural sciences - Aczel, Balazs; Szaszi, Barnabas; Clelland, Harry T.; Kovacs, Marton; Holzmeister, Felix; van Ravenzwaaij, Don; Schulz-Kümpel, Hannah; Hoffmann, Sabine; Nilsonne, Gustav; Kosa, Livia; Torma, Zoltan A.; Abdelfatah, Yousuf; et al. (Nature, 2026)
The same dataset can be analysed in different justifiable ways to answer the same research question, potentially challenging the robustness of empirical science1-3. In this crowd initiative, we investigated the degree to which research findings in the social and behavioural sciences are contingent on analysts' choices. We examined a stratified random sample of 100 studies published between 2009 and 2018, in which, for one claim per study, at least five reanalysts independently reanalysed the original data. The statistical appropriateness of the reanalyses was assessed in peer evaluations, and the robustness indicators were inspected along a range of research characteristics and study designs. We found that 34% of the independent reanalyses yielded the same result (within a tolerance region of ±0.05 Cohen's d) as the original report; with a four times broader tolerance region, this indicator increased to 57%. Of the reanalyses conducted, 74% reached the same conclusion as the original investigation, 24% yielded no effects or inconclusive results and 2% reported the opposite effect. This exploratory study indicates that the common single-path analyses in social and behavioural research should not be simply assumed to be robust to alternative analyses4. Therefore, we recommend the development and use of practices to explore and communicate this neglected source of uncertainty. © 2026. The Author(s), under exclusive licence to Springer Nature Limited.
Keywords: Behavioural sciences; Empirical research; Exploratory research; Robustness (evolution); Sample size determination; Statistical analysis; dept.psy

General trait and workplace fear of missing out (FoMO) and the neurodiverse mind: Exploring autism, ADHD, and internal representation profiles - McKee, Paul; Boulhadi, Khaoula; Nadelhoffer, Thomas (Personality and Individual Differences, 2026)
Keywords: Mental representation; Psychometrics; Representation (politics); Social perception; Trait; dept.psy

Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (Functional Ecology, 2026)
Abstract Understanding the thermal sensitivity of reproductive interactions is crucial given global warming. Previous studies have almost exclusively focused on interactions before mating, even though important interactions between the sexes also occur after mating (e.g. gamete interactions), which are likely also affected by temperature. Thus, it remains unknown how temperature affects the influence of female reproductive fluid on sperm performance, thereby altering female control over fertilization (cryptic female choice). This gap limits our understanding of how sexual selection changes with seasonal temperature fluctuations and temperatures outside the range of historical norms. We tested how temperatures relevant to current conditions and climate change projections influence the mechanisms underlying cryptic female choice in a marine fish, Symphodus ocellatus . Under typical, cooler thermal conditions, female reproductive fluid enhances sperm velocity and biases fertilization dynamics to favour preferred, dominant males over sneaker males. We find that warmer temperatures decrease female influence on sperm velocity, especially for dominant males. This results in dominant males having slower sperm than sneaker males at warmer temperatures, reducing the expected paternity of preferred, dominant males. Our results highlight that considering the thermal sensitivity of female–male interactions that occur after mating will be essential for understanding how seasonal variation and climate change can influence fertility, reproduction and sexual selection. Read the free Plain Language Summary for this article on the Journal blog.
Keywords: Gamete; Mating; Mating system; Reproduction; Reproductive success; Sexual selection; Sperm; Sperm competition; alternative reproductive tactics; climate change; dept.psy; mating systems; ovarian fluid; sexual selection; sperm competition; thermal ecology

Actigraphy-based sleep outcomes in substance use disorders: A protocol for a systematic review and meta-analysis - Naveda, Alisson; Oliva, Henrique; Ghadimi, Delaram; Angarita, Gustavo (PLoS ONE, 2026)
INTRODUCTION: Individuals with substance use disorders (SUDs) are at increased risk for sleep disturbances, creating a bidirectional relationship that may heighten relapse risk. While polysomnography is the gold standard for measuring sleep, many studies have used actigraphy, a noninvasive, wrist-worn device that estimates rest-activity patterns and sleep-wake characteristics. Despite its utility, the use of actigraphy in populations with SUDs remains limited, and findings vary across substances and methodologies. This protocol outlines a systematic review and meta-analysis aiming to synthesize evidence on actigraphy-derived sleep outcomes across various substances. METHOD AND ANALYSIS: We will include peer-reviewed observational or interventional studies involving individuals aged 18 or older with a diagnosis of substance use (e.g., alcohol, benzodiazepines, cannabis, cocaine, opioids, methamphetamine, or nicotine) who use actigraphy to assess sleep compared to matched controls. Studies will be excluded during screening if they do not use actigraphy, do not include populations with SUDs, or focus on participants younger than 18. There will be no restrictions on location, setting, or language. Databases to be searched include PubMed, Scopus, Web of Science, ProQuest, ClinicalTrials.gov, CINAHL, PsycINFO, and Embase. Titles and abstracts will be screened in the first phase, followed by full-text screening using eligibility criteria. At least two independent reviewers will assess risk of bias using the Risk Of Bias In Non-randomized Studies of Exposures (ROBINS-E) tool. A synthesis will summarize key findings, including study characteristics, population differences, and methodological variations. DISCUSSION: This review will offer a clear and comprehensive assessment of the current literature on actigraphy to examine sleep in SUD and to inform future research to study sleep and its implications in SUD populations. PROTOCOL REGISTRATION NUMBER: International Prospective Register for Systematic Reviews (PROSPERO) number CRD420251072028.
Keywords: MEDLINE; Prospective cohort study; Protocol (science); Substance use; Systematic review; dept.psy

Conflict and cooperation in male–male partnerships alter paternal care behavior in the ocellated wrasse - Hellmann, Jennifer; Stiver, Kelly; Marsh‐Rollo, Susan; Alonzo, Suzanne (Behavioral Ecology, 2025)
Keywords: Biology; Fish; Fishery; Genetics; Paternal care; Symphodus ocellatus; Wrasse; Zoology; dept.psy; parental care; plasticity; reproduction; sexual selection; temperature

Breaking the truth bias: the impact of comparable truth baselines and reality interview on veracity judgments by laypeople and police officers - Bogaard, Glynis; Nieuwkamp, Veerle; Colwell, Kevin (Police Practice and Research, 2025)
This study examined whether embedding baselining within the Reality Interview (RI) protocol enhances intuitive veracity judgments. Baselining involves using a person's truthful verbal behavior as a reference point for evaluating the veracity of subsequent statements. We hypothesized that access to a comparable truth baseline (CTB) would improve veracity judgment accuracy. Eyewitnesses of a mock crime were interviewed with the RI and instructed to respond either honestly or deceptively. Laypeople (Experiment 1) and police officers (Experiment 2) evaluated these statements with or without a CTB. With a CTB, laypeople showed significantly higher accuracy in detecting deception and a reduced truth bias. However, police officers showed no improvement, maintaining chance-level performance regardless of statement veracity. These findings suggest that CTBs enhance lie detection in laypeople but not in trained professionals. Future research should explore tailored approaches to improving veracity judgments, perhaps incorporating specific guidelines on how to best use available cues.
Keywords: Baseline (sea); Comparable Truth Baseline; Deception; Interview; Lie detection; Point (geometry); Protocol (science); Reality Interview; Statement (logic); Trustworthiness; dept.psy; lie detection; verbal cues

Pharmacotherapies for stimulant use disorder and co-occurring attention deficit hyperactivity disorder: protocol for a systematic review and a meta-analysis - Oliva, Henrique; Pulido-Saavedra, Alejandra; Paredes-Naveda, Alisson; Forselius, Emerson; Potenza, Marc; Jegede, Oluwole; Angarita, Gustavo (Frontiers in Psychiatry, 2025)
Background Stimulant use disorder (StUD) and attention-deficit/hyperactivity disorder (ADHD) frequently co-occur. This comorbidity complicates treatment and worsens clinical outcomes. Despite the high prevalence, shared vulnerability and clinical relevance of this comorbidity, evidence on effective pharmacotherapies among individuals with this dual diagnosis remains limited. Materials and methods This systematic review protocol is reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) statement and will include randomized controlled trials involving adults with comorbid StUD (cocaine, amphetamines, or methamphetamines) and ADHD. The following databases will be searched: PubMed, Embase, Scopus, and Web of Science. Covidence will be used to support independent screening and data extraction. Two reviewers will independently screen studies (title/abstract and full text). One author will extract data, which will be independently verified by a second reviewer. Quality assessment of included articles will be assessed using the Cochrane Risk of Bias instrument, and certainty of the evidence for each outcome will be assessed using Grading of Recommendations, Assessment, Development and Evaluations (GRADE) methodology. Primary outcomes include duration of continuous abstinence, odds of stimulant-negative urine samples, ADHD symptom changes, and medication adverse events. Where feasible, meta-analyses will be conducted using random-effects models. Significance and dissemination This review will synthesize existing evidence on the efficacy of pharmacotherapies (stimulants and non-stimulants) for individuals with co-occurring StUD and ADHD. The results of this study will likely inform clinical practice by evaluating outcomes such as reduction in stimulant use and abstinence, and improvement in ADHD symptoms. Findings will be disseminated through peer-reviewed publication and presentations to reach both clinical and academic audiences. Systematic review registration PROSPERO, CRD420250655356.
Keywords: Alternative medicine; Atomoxetine; Attention deficit hyperactivity disorder; Clinical psychology; Internal medicine; Medicine; Meta-analysis; Methylphenidate; Protocol (science); Psychiatry; Psychology; Stimulant; attention deficit hyperactivity disorder; co-occurring disorder; cocaine; dept.psy; methamphetamine; stimulant use disorder

Masked-Speech Recognition and Self-Reported Functional Listening in Autistic Young Adults - Wasiuk, Peter; Cook, Barbara; Irwin, Julia (Journal of Speech Language and Hearing Research, 2025)
Keywords: Active listening; Audiology; Autism; Cognitive psychology; Communication; Developmental psychology; Medicine; Perception; Psychology; Speech perception; dept.cmd; dept.psy

Writing Wisdom, Reviewing Identity: Positive Outcomes of Participating in a Memoir Course for Older Adults - Bivona, Marissa A.; Kahlbaugh, Patricia E.; Budnick, Christopher J. (The International Journal of Reminiscence and Life Review, 2020)
Constructing a personal narrative and consolidating identity is an ongoing process that becomes pressing in the face of mortality. The current pilot study examined the process of life review in a sample of older people, specifically examining the effects of participation in a memoir course on wisdom, identity, and well-being. We hypothesized that wisdom, identity fidelity and coherence, and subjective well-being would increase for those in the memoir group compared to a control. Eighteen elderly individuals from two senior retirement communities were randomly assigned to participate in weekly classes, for four weeks, either to work on a memoir or discuss films (control group). After engaging in the process of organizing their life story and writing about important memories, the nine individuals in the memoir group scored significantly higher on self-report measures of wise reminiscence, identity fidelity, and subjective well-being compared to those in the control group. Furthermore, exploratory analyses found that wise reminiscence statistically mediated relationships between the memoir condition and the outcome measures of identity fidelity, identity coherence, and subjective well-being. These findings point to the benefits of memoir writing for positive aging as well as potential mechanisms underlying its effectiveness.
Keywords: Identity; Life Review; Narrative; Subjective Well-Being; Wisdom; dept.psy

Attitudes About Aging and Beliefs About When you Have Been or Will be Your Best Self - Kahlbaugh, Patricia; Biblekaj, Viktoria; Shortell, Malori (The International Journal of Aging and Human Development, 2025)
Keywords: Anxiety; Clinical psychology; Developmental psychology; Gerontology; Healthy aging; Internalization; Medicine; Psychiatry; Psychology; Successful aging; dept.psy; peer-reviewed

Fear of Missing Out’s (FoMO) relationship with moral judgment and behavior - McKee, Paul C.; Senthilnathan, Ithika; Budnick, Christopher J.; Bind, Marie-Abèle; Antonios, Imad; Sinnott-Armstrong, Walter (PLOS ONE, 2024)
Across three online studies, we examined the relationship between the Fear of Missing Out (FoMO) and moral cognition and behavior. Study 1 (N = 283) examined whether FoMO influenced moral awareness, judgments, and recalled and predicted behavior of first-person moral violations in either higher or lower social settings. Study 2 (N = 821) examined these relationships in third-person judgments with varying agent identities in relation to the participant (agent = stranger, friend, or someone disliked). Study 3 (N = 604) examined the influence of recalling activities either engaged in or missed out on these relationships. Using the Rubin Causal Model, we created hypothetical randomized experiments from our real-world randomized experimental data with treatment conditions for lower or higher FoMO (median split), matched for relevant covariates, and compared differences in FoMO groups on moral awareness, judgments, and several other behavioral outcomes. Using a randomization-based approach, we examined these relationships with Fisher Tests and computed 95% Fisherian intervals for constant treatment effects consistent with the matched data and the hypothetical FoMO intervention. All three studies provide evidence that FoMO is robustly related to giving less severe judgments of moral violations. Moreover, those with higher FoMO were found to report a greater likelihood of committing moral violations in the past, knowing people who have committed moral violations in the past, being more likely to commit them in the future, and knowing people who are likely to commit moral violations in the future.
Keywords: Behavior; Interpersonal relationships; Machine learning; Memory recall; Moral philosophy; Personality; Religion; Social media; dept.csc; dept.psy; peer-reviewed

Using the Listening2Faces App with Three Young Adults with Autism: A Feasibility Study - Baron, Alisa; Harwood, Vanessa; Woodard, Cooper; Anderson, Kaitlyn; Fernandes, Barbara; Sullivan, Jessica; Irwin, Julia (Advances in Neurodevelopmental Disorders, 2024)
Abstract Objectives Listening2Faces (L2F) is a therapeutic, application-based training program designed to improve audiovisual speech perception for persons with communication disorders. The purpose of this research was to investigate the feasibility of using the L2F application with young adults with autism and complex communication needs. Methods Three young adults with autism and complex communication needs completed baseline assessments and participated in training sessions within the L2F application. Behavioral supports, including the use of cognitive picture rehearsal, were used to support engagement with the L2F application. Descriptive statistics were used to provide (1) an overview of the level of participation in L2F application with the use of behavioral supports and (2) general performance on L2F application for each participant. Results All three participants completed the initial auditory noise assessment (ANA) as well as 8 or more levels of the L2F application with varying accuracy levels. One participant completed the entire L2F program successfully. Several behavioral supports were used to facilitate participation; however, each individual demonstrated varied levels of engagement with the application. Conclusions The L2F application may be a viable intervention tool to support audiovisual speech perception in persons with complex communication needs within a school-based setting. A review of behavioral supports and possible beneficial modifications to the L2F application for persons with complex communication needs are discussed.
Keywords: dept.psy; peer-reviewed

Sleep Health among Children Adopted from Foster Care: The Moderating Effect of Parent–Child Sleep Interactions - Cifre, Anthony B.; Budnick, Christopher J.; Bick, Johanna; McGlinchey, Eleanor L.; Ripple, Carol H.; Wolfson, Amy R.; Alfano, Candice A. (Behavioral Sleep Medicine, 2024)
Keywords: dept.psy; peer-reviewed

A review of the kappa opioid receptor system in opioid use - Cayir, Salih; Zhornitsky, Simon; Barzegary, Alireza; Sotomayor-Carreño, Esteban; Sarfo-Ansah, Wonder; Funaro, Melissa C.; Matuskey, David; Angarita, Gustavo (Neuroscience & Biobehavioral Reviews, 2024)
The kappa opioid receptor (KOR) system is implicated in dysphoria and as an “anti-reward system” during withdrawal from opioids. However, no clear consensus has been made in the field, as mixed findings have been reported regarding the relationship between the KOR system and opioid use. This review summarizes the studies to date on the KOR system and opioids. A systematic scoping review was reported following PRISMA guidelines and conducted based on the published protocol. Comprehensive searches of several databases were done in the following databases: MEDLINE, Embase, PsycINFO, Web of Science, Scopus, and Cochrane. We included preclinical and clinical studies that tested the administration of KOR agonists/antagonists or dynorphin and/or measured dynorphin levels or KOR expression during opioid intoxication or withdrawal from opioids. One hundred studies were included in the final analysis. Preclinical administration of KOR agonists decreased drug-seeking/taking behaviors and opioid withdrawal symptoms. KOR antagonists showed mixed findings, depending on the agent and/or type of withdrawal symptom. Administration of dynorphins attenuated opioid withdrawal symptoms both in preclinical and clinical studies. In the limited number of available studies, dynorphin levels were found to increase in cerebrospinal fluid (CSF) and peripheral blood lymphocytes (PBL) of opioid use disorder subjects (OUD). In animals, dynorphin levels and/or KOR expression showed mixed findings during opioid use. The KOR/dynorphin system appears to have a multifaceted and complex nature rather than simply functioning as an anti-reward system. Future research in well-controlled study settings is necessary to better understand the clinical role of the KOR system in opioid use.
Keywords: Dynorphins; Opioid use disorder; Opioids; dept.psy; peer-reviewed; κ-opioid receptor

Best Darn Statistics Workbook Ever - Hauselt, William J.; Mugno, Raymond (Kendall Hunt Publishing, 2021)
Keywords: dept.mat; dept.psy

Age differences in emotional reactions to ageist memes and changes in age of one's Best Self - Kahlbaugh, Patricia; Ramos-Arvelo, Jacklyn; Brenning, Madison; Huffman, Loreen (Journal of Aging Studies, 2024)
Memes on social media can carry ageist messages and can elicit reactions that are both emotional and self-evaluative. The present study investigates age-related differences in nine discrete emotions and in the evaluation of when individuals have been or will be their best selves. Participants (n = 360) representing young (m = 26 years), middle-aged (m = 39 years) and older adults (m = 63 years) were randomly assigned to view either non-ageist (animals) or ageist (e.g., incompetent older people) memes. After viewing memes, we assessed nine emotional reactions (i.e., fear, anger, sadness, happiness, anxiety, discomfort, disgust, surprise, enjoyment) and Best Self evaluations. Younger and middle-aged people reported more intense emotional reactions to memes than older people, with the exception that older people reported more discomfort and disgust in response to ageist versus non-ageist memes. Younger adults were less surprised by ageist memes (vs. non-ageist) and for all age groups ageist memes (vs. non-ageist) elicited less happiness and enjoyment and were less likely to be shared. With respect to evaluations of one's Best Self, older individuals were more likely to report being their best selves in the past, while after viewing ageist memes, younger individuals were more likely to report being their best selves in the future. Emotions of disgust and discomfort were related to identifying one's Best Self as further in the past. The current study adds to the literature on the impact of ageism by examining age-related differences in the emotions and self-evaluations experienced when confronted with memes on social media.
Keywords: Ageism; Emotions; Self-evaluations; Social media/memes; dept.psy; peer-reviewed

Assessing the efficacy of baselining in deception detection: A comparative analysis of the reality interview and structured interview - Bogaard, Glynis; van de Bovekamp, Anne Margreet; Colwell, Kevin (Acta Psychologica, 2024)
Detecting deception is challenging; there exists no universal cue that gives away deceit and people vary greatly in how they communicate. One way to potentially improve deception detection is by comparing multiple responses of the same individual to identify verbal deviations – a method known as baselining. This study examined the impact of baselining embedded in a specific interview protocol to improve lie detection. Participants (N = 179) viewed mock crimes and were instructed to lie or tell the truth about what they witnessed. Next, they were interviewed including a truthful baseline (Reality Interview Modified: RIM), or no baseline (Reality Interview: RI; Structured Interview: SI). Results showed that truth tellers in the SI and RI conditions provided more details than liars during free recall, while no detail differences emerged for the RIM condition. Follow-up questions in all conditions showed truth tellers offered more details than liars. Surprisingly, we found no evidence that verbal deviations from a baseline can be used as effective indicators of deception. In sum, further research is needed to explore the best application of baselining for lie detection purposes.
Keywords: Baselining; Deception detection; Reality interview; Verbal cues; dept.psy; peer-reviewed

Preliminary Findings From the Hearing Assessment in Response to Noise Screener: A New Pediatric Tool for Measuring Speech Identification in Noise - Irwin, Julia; Sullivan, Jessica; Fernandes, Barbara; Lotto, Alyssa (Perspectives of the ASHA Special Interest Groups, 2023)
Purpose: As part of the development of a speech-in-noise screener, speech recognition was measured in quiet and in an interrupted noise for 59 children with typical development according to parent report. Method: There were 39 monolingual and 20 bilingual participants. A corpus of 107 words were presented by a male and female speaker and present in the following conditions: +3 dB signal-to- noise ratio (SNR), −3 dB SNR, and quiet. Results: The participants showed increasing difficulty with speech identification as the SNR decreased. Additionally, age-related differences in accuracy were observed at each noise level. Conclusion: Our findings provide preliminary support for the utility and efficacy of a speech-in-noise screener for use with children.
Keywords: SCSU-student; dept.psy

The role of combat exposure on drinking behavior and subjective well-being: A Rubin Causal Model approach. - McKee, Paul; Budnick, Christopher J.; Walters, Kenneth S.; Bind, Marie-Abèle (Psychological Trauma: Theory, Research, Practice, and Policy, 2024)
Keywords: dept.psy; peer-reviewed

Social Environment Influences the Temporal Dynamics of Sneak-Spawning in a Fish with Alternative Reproductive Tactics - Kustra, Matthew C.; Stiver, Kelly A.; Marsh-Rollo, Susan; Hellmann, Jennifer K.; Alonzo, Suzanne H. (The American Naturalist, 2023)
Several predictions of sperm competition theory are not well supported empirically. One potential reason is that most current theory and empirical research ignore how the social environment influence the temporal dynamics of mating. We propose that understanding these dynamics is key to understanding sexual selection and improving the predictive power of theory. To demonstrate the importance of these dynamics, we quantify how males’ social role, interactions among males, and current social environment influence the timing of mating in Symphodus ocellatus, a species with three alternative male reproductive tactics. Nesting males spawn synchronously with females; sneakers and satellites sneak-spawn with some time delay. Satellites also cooperate with nesting males. We found that satellites have shorter sneak-spawning delays than sneakers, a benefit of their cooperation with nesting males. Sneak-spawning delays decreased with increasing nest activity for sneakers but not for satellites, suggesting that sneakers may benefit from increased sperm competition intensity. Current sperm competition models ignore this potential benefit, which may be why the prediction that males should decrease investment when sperm competition involves more than two males is not well supported. Our study provides insight into mechanisms that drive variation in the timing of spawning, which could explain mismatches between theoretical and empirical results.
Keywords: alternative mating tactics; cooperation; dept.psy; peer-reviewed; reproductive competition; sexual selection; sneak-spawning; sperm competition

Developmental Themes in the Narrative of Adults with Early International Experiences - Abe, Jo Ann A. (Journal of Adult Development, 2023)
This study extends research on adult narrative identity in two major ways. First, it focuses on Adult Third Culture Kids (ATCKs), which refer to individuals who spent a part of their early developmental years abroad. In spite of the fact that they are an important demographic to study in this rapidly globalizing world, they have tended to be neglected in the field of psychology. Second, this study incorporates the cutting-edge tools of automated language analysis to extract developmental themes from autobiographical narratives using a bottom-up exploratory approach, as well as to identify psychological patterns and processes associated with the themes. The participants (N = 350; 18–80 + years old) were recruited from an alumni office of an international school and asked to write a narrative about the impact their international experiences had on their development. The meaning extraction method (MEM) yielded four developmental themes, which were remarkably consistent with the recurring themes that emerge from past research on adult narrative identity as well as ATCKs: past focus, communion, agency, and global focus. These four developmental themes, in turn, showed theoretically coherent patterns of relations with the demographic variables, linguistic markers of psychological patterns and processes, as well as self-reports of dimensions of well-being.
Keywords: Adult third culture kids (ATCKs); LIWC; MEH; Meaning extraction method; Narrative identity; dept.psy; peer-reviewed

Event-Related Potentials in Assessing Visual Speech Cues in the Broader Autism Phenotype: Evidence from a Phonemic Restoration Paradigm - Harwood, Vanessa; Baron, Alisa; Kleinman, Daniel; Campanelli, Luca; Irwin, Julia; Landi, Nicole (Brain Sciences, 2023)
Audiovisual speech perception includes the simultaneous processing of auditory and visual speech. Deficits in audiovisual speech perception are reported in autistic individuals; however, less is known regarding audiovisual speech perception within the broader autism phenotype (BAP), which includes individuals with elevated, yet subclinical, levels of autistic traits. We investigate the neural indices of audiovisual speech perception in adults exhibiting a range of autism-like traits using event-related potentials (ERPs) in a phonemic restoration paradigm. In this paradigm, we consider conditions where speech articulators (mouth and jaw) are present (AV condition) and obscured by a pixelated mask (PX condition). These two face conditions were included in both passive (simply viewing a speaking face) and active (participants were required to press a button for a specific consonant–vowel stimulus) experiments. The results revealed an N100 ERP component which was present for all listening contexts and conditions; however, it was attenuated in the active AV condition where participants were able to view the speaker’s face, including the mouth and jaw. The P300 ERP component was present within the active experiment only, and significantly greater within the AV condition compared to the PX condition. This suggests increased neural effort for detecting deviant stimuli when visible articulation was present and visual influence on perception. Finally, the P300 response was negatively correlated with autism-like traits, suggesting that higher autistic traits were associated with generally smaller P300 responses in the active AV and PX conditions. The conclusions support the finding that atypical audiovisual processing may be characteristic of the BAP in adults.
Keywords: audiovisual; dept.psy; event-related potentials; peer-reviewed; phonemic restoration; speech perception

Neural and Behavioral Differences in Speech Perception for Children With Autism Spectrum Disorders Within an Audiovisual Context - Irwin, Julia; Harwood, Vanessa; Kleinman, Daniel; Baron, Alisa; Avery, Trey; Turcios, Jacqueline; Landi, Nicole (Journal of Speech, Language, and Hearing Research, 2023)
Purpose: Reduced use of visible articulatory information on a speaker's face has been implicated as a possible contributor to language deficits in autism spectrum disorders (ASD). We employ an audiovisual (AV) phonemic restoration paradigm to measure behavioral performance (button press) and event-related potentials (ERPs) of visual speech perception in children with ASD and their neurotypical peers to assess potential neural substrates that contribute to group differences. Method: Two sets of speech stimuli, /ba/–“/a/” (“/a/” was created from the /ba/ token by a reducing the initial consonant) and /ba/–/pa/, were presented within an auditory oddball paradigm to children aged 6–13 years with ASD (n = 17) and typical development (TD; n = 33) within two conditions. The AV condition contained a fully visible speaking face; the pixelated (PX) condition included a face, but the mouth and jaw were PX, removing all articulatory information. When articulatory features were present for the /ba/–“/a/” contrast, it was expected that the influence of the visual articulators would facilitate a phonemic restoration effect in which “/a/” would be perceived as /ba/. ERPs were recorded during the experiment while children were required to press a button for the deviant sound for both sets of speech contrasts within both conditions. Results: Button press data revealed that TD children were more accurate in discriminating between /ba/–“/a/” and /ba/–/pa/ contrasts in the PX condition relative to the ASD group. ERPs in response to the /ba/–/pa/ contrast within both AV and PX conditions differed between children with ASD and TD children (earlier P300 responses for children with ASD). Conclusion: Children with ASD differ in the underlying neural mechanisms responsible for speech processing compared with TD peers within an AV context.
Keywords: dept.psy; peer-reviewed

Where on the face do we look during phonemic restoration: An eye-tracking study - Baron, Alisa; Harwood, Vanessa; Kleinman, Daniel; Campanelli, Luca; Molski, Joseph; Landi, Nicole; Irwin, Julia (Frontiers in Psychology, 2023)
Face to face communication typically involves audio and visual components to the speech signal. To examine the effect of task demands on gaze patterns in response to a speaking face, adults participated in two eye-tracking experiments with an audiovisual (articulatory information from the mouth was visible) and a pixelated condition (articulatory information was not visible). Further, task demands were manipulated by having listeners respond in a passive (no response) or an active (button press response) context. The active experiment required participants to discriminate between speech stimuli and was designed to mimic environmental situations which require one to use visual information to disambiguate the speaker’s message, simulating different listening conditions in real-world settings. Stimuli included a clear exemplar of the syllable /ba/ and a second exemplar in which the formant initial consonant was reduced creating an /a/−like consonant. Consistent with our hypothesis, results revealed that the greatest fixations to the mouth were present in the audiovisual active experiment and visual articulatory information led to a phonemic restoration effect for the /a/ speech token. In the pixelated condition, participants fixated on the eyes, and discrimination of the deviant token within the active experiment was significantly greater than the audiovisual condition. These results suggest that when required to disambiguate changes in speech, adults may look to the mouth for additional cues to support processing when it is available.
Keywords: dept.psy; peer-reviewed

Motivation states to move, be physically active and sedentary vary like circadian rhythms and are associated with affect and arousal - Budnick, Christopher J.; Stults-Kolehmainen, Matthew; Dadina, Cyrus; Bartholomew, John B.; Boullosa, Daniel; Ash, Garret I.; Sinha, Rajita; Blacutt, Miguel; Haughton, Adrian; Lu, Tom (Frontiers in Sports and Active Living, 2023)
IntroductionMotivation to be physically active and sedentary is a transient state that varies in response to previous behavior. It is not known: (a) if motivational states vary from morning to evening, (b) if they are related to feeling states (arousal/hedonic tone), and (c) whether they predict current behavior and intentions. The primary purpose of this study was to determine if motivation states vary across the day and in what pattern. Thirty adults from the United States were recruited from Amazon MTurk.MethodsParticipants completed 6 identical online surveys each day for 8 days beginning after waking and every 2–3 h thereafter until bedtime. Participants completed: (a) the CRAVE scale (Right now version) to measure motivation states for Move and Rest, (b) Feeling Scale, (c) Felt Arousal Scale, and (d) surveys about current movement behavior (e.g., currently sitting, standing, laying down) and intentions for exercise and sleep. Of these, 21 participants (mean age 37.7 y; 52.4% female) had complete and valid data.ResultsVisual inspection of data determined that: a) motivation states varied widely across the day, and b) most participants had a single wave cycle each day. Hierarchical linear modelling revealed that there were significant linear and quadratic time trends for both Move and Rest. Move peaked near 1500 h when Rest was at its nadir. Cosinor analysis determined that the functional waveform was circadian for Move for 81% of participants and 62% for Rest. Pleasure/displeasure and arousal independently predicted motivation states (all p's < .001), but arousal had an association twice as large. Eating, exercise and sleep behaviors, especially those over 2 h before assessment, predicted current motivation states. Move-motivation predicted current body position (e.g., laying down, sitting, walking) and intentions for exercise and sleep more consistently than rest, with the strongest prediction of behaviors planned for the next 30 min.DiscussionWhile these data must be replicated with a larger sample, results suggest that motivation states to be active or sedentary have a circadian waveform for most people and influence future behavioral intentions. These novel results highlight the need to rethink the traditional approaches typically utilized to increase physical activity levels.
Keywords: dept.psy; peer-reviewed

Qualitative and quantitative evidence of motivation states for physical activity, exercise and being sedentary from university student focus groups - Stults-Kolehmainen, Matthew A.; Gilson, Todd A.; SantaBarbara, Nicholas; McKee, Paul C.; Sinha, Rajita; Bartholomew, John B.; Boullosa, Daniel; Budnick, Christopher J.; Bueno, Fabio Amador; Haughton, Adrian; Barker, Jessica L.; Ash, Garrett I. (Frontiers in Sports and Active Living, 2023)
Motivation for physical activity and sedentary behaviors (e.g., desires, urges, wants, cravings) varies from moment to moment. According to the WANT model, these motivation states may be affectively-charged (e.g., felt as tension), particularly after periods of maximal exercise or extended rest. The purpose of this study was to examine postulates of the WANT model utilizing a mixed-methods approach. We hypothesized that: (1) qualitative evidence would emerge from interviews to support this model, and (2) motivation states would quantitatively change over the course of an interview period. Seventeen undergraduate students (mean age = 18.6y, 13 women) engaged in focus groups where 12 structured questions were presented. Participants completed the “right now” version of the CRAVE scale before and after interviews. Qualitative data were analyzed with content analysis. A total of 410 unique lower-order themes were classified and grouped into 43 higher order themes (HOTs). From HOTs, six super higher order themes (SHOTs) were designated: (1) wants and aversions, (2) change and stability, (3) autonomy and automaticity, (4) objectives and impulses, (5) restraining and propelling forces, and (6) stress and boredom. Participants stated that they experienced desires to move and rest, including during the interview, but these states changed rapidly and varied both randomly as well as systematically across periods of minutes to months. Some also described a total absence of desire or even aversion to move and rest. Of note, strong urges and cravings for movement, typically from conditions of deprivation (e.g., sudden withdrawal from exercise training) were associated with physical and mental manifestations, such as fidgeting and feeling restless. Urges were often consummated with behavior (e.g., exercise sessions, naps), which commonly resulted in satiation and subsequent drop in desire. Importantly, stress was frequently described as both an inhibitor and instigator of motivation states. CRAVE-Move increased pre-to-post interviews (p < .01). CRAVE-Rest demonstrated a trend to decline (p = .057). Overall, qualitative and quantitative data largely corroborated postulates of the WANT model, demonstrating that people experience wants and cravings to move and rest, and that these states appear to fluctuate significantly, especially in the context of stress, boredom, satiety, and deprivation.
Keywords: dept.psy; peer-reviewed

College student Fear of Missing Out (FoMO) and maladaptive behavior: Traditional statistical modeling and predictive analysis using machine learning - McKee, Paul C.; Budnick, Christopher J.; Walters, Kenneth S.; Antonios, Imad (PLOS ONE, 2022)
This paper reports a two-part study examining the relationship between fear of missing out (FoMO) and maladaptive behaviors in college students. This project used a cross-sectional study to examine whether college student FoMO predicts maladaptive behaviors across a range of domains (e.g., alcohol and drug use, academic misconduct, illegal behavior). Participants (N = 472) completed hard copy questionnaire packets assessing trait FoMO levels and questions pertaining to unethical and illegal behavior while in college. Part 1 utilized traditional statistical analyses (i.e., hierarchical regression modeling) to identify any relationships between FoMO, demographic variables (socioeconomic status, living situation, and gender) and the behavioral outcomes of interest. Part 2 looked to quantify the predictive power of FoMO, and demographic variables used in Part 1 through the convergent approach of supervised machine learning. Results from Part 1 indicate that college student FoMO is indeed related to many diverse maladaptive behaviors spanning the legal and illegal spectrum. Part 2, using various techniques such as recursive feature elimination (RFE) and principal component analysis (PCA) and models such as logistic regression, random forest, and Support Vector Machine (SVM), showcased the predictive power of implementing machine learning. Class membership for these behaviors (offender vs. non-offender) was predicted at rates well above baseline (e.g., 50% at baseline vs 87% accuracy for academic misconduct with just three input variables). This study demonstrated FoMO’s relationships with these behaviors as well as how machine learning can provide additional predictive insights that would not be possible through inferential statistical modeling approaches typically employed in psychology, and more broadly, the social sciences. Research in the social sciences stands to gain from regularly utilizing the more traditional statistical approaches in tandem with machine learning.
Keywords: Alcohol consumption; Behavior; Cannabis; Drug interactions; Forecasting; Machine learning; Machine learning algorithms; Principal component analysis; dept.csc; dept.psy; peer-reviewed

Empowering Young Readers: Dialogic Reading with Integrated Vocabulary Enrichment - Moore, Dina; Durwin, Cheryl C. (Rowman & Littlefield Publishers, 2022)
Keywords: dept.psy

Urges to Move and Other Motivation States for Physical Activity in Clinical and Healthy Populations: A Scoping Review Protocol - Stults-Kolehmainen, Matthew A.; Blacutt, Miguel; Bartholomew, John B.; Boullosa, Daniel; Janata, Petr; Koo, Brian B.; McKee, Paul C.; Casper, Regina; Budnick, Christopher J.; Gilson, Todd A.; Blakemore, Rebekah L.; Filgueiras, Alberto; et al. (Frontiers in Psychology, 2022)
Motivation for bodily movement, physical activity and exercise varies from moment to moment. These motivation states may be “affectively-charged,” ranging from instances of lower tension (e.g., desires, wants) to higher tension (e.g., cravings and urges). Currently, it is not known how often these states have been investigated in clinical populations (e.g., eating disorders, exercise dependence/addiction, Restless Legs Syndrome, diabetes, obesity) vs. healthy populations (e.g., in studies of motor control; groove in music psychology). The objective of this scoping review protocol is to quantify the literature on motivation states, to determine what topical areas are represented in investigations of clinical and healthy populations, and to discover pertinent details, such as instrumentation, terminology, theories, and conceptual models, correlates and mechanisms of action. Iterative searches of scholarly databases will take place to determine which combination of search terms (e.g., “motivation states” and “physical activity”; “desire to be physically active,” etc.) captures the greatest number of relevant results. Studies will be included if motivation states for movement (e.g., desires, urges) are specifically measured or addressed. Studies will be excluded if referring to motivation as a trait. A charting data form was developed to scan all relevant documents for later data extraction. The primary outcome is simply the extent of the literature on the topic. Results will be stratified by population/condition. This scoping review will unify a diverse literature, which may result in the creation of unique models or paradigms that can be utilized to better understand motivation for bodily movement and exercise.
Keywords: dept.psy; peer-reviewed

Cognitive-Affective Styles of Biden and Trump Supporters: An Automated Text Analysis Study - Abe, Jo Ann A. (Social Psychological and Personality Science, 2022)
Are conservatives more simple-minded and happier than liberals? To revisit this question, 1,518 demographically diverse participants (52% females) were recruited from an online participant-sourcing platform and asked to write a narrative about the upcoming 2020 U.S. Presidential Election as well as complete self and candidates’ ratings of personality. The narratives were analyzed using three well-validated text analysis programs. As expected, extremely enthusiastic Trump supporters used less cognitively complex and more confident language than both their less enthusiastic counterparts and Biden supporters. Trump supporters also used more positive affective language than Biden supporters. More simplistic and categorical modes of thinking as well as positive emotional tone were also associated with positive perceptions of Trump’s, but not Biden’s personality. Dialectical complexity and positive emotional tone accounted for significant unique variance in predicting appraisals of Trump’s trustworthiness/integrity even after controlling for demographic variables, self-ratings of conscientiousness and openness, and political affiliation.
Keywords: AutoIC; FFM; LIWC; cognitive-affective styles; dept.psy; peer-reviewed; political preferences

Navigating Ethical Challenges for Pediatric Sickle Cell Pain Management in the Context of the Opioid Epidemic - Mulchan, Siddika S.; Wakefield, Emily O.; Martin, Sarah R.; Ayr-Volta, Lauren; Krenicki, Kayla; Zempsky, William T. (The Clinical Journal of Pain, 2022)
Objectives: The aim was to describe the impact of the opioid epidemic on pain management practices in pediatric sickle cell disease (SCD) and propose a conceptual framework for navigating ethical decision-making in pediatric sickle cell pain management. Methods: A review of the literature on ethical challenges in the management of sickle cell pain was conducted and considered in the context of the opioid epidemic and psychosocial factors affecting youth with SCD. The Integrated Ethical Framework for Pain Management (IEFPM) was applied to pediatric sickle cell pain management using a clinical case example. Results: Implicit bias, health-related stigma, and potential neurocognitive impairment all present unique challenges in ethical decision-making for youth with SCD. National guidelines for prescribing opioid medication may complicate providers’ clinical decision-making and affect their sickle cell pain management practices. The IEFPM was found to be applicable to ethical decision-making for pediatric sickle cell pain and captures both patient-related and provider-related aspects of clinical pain management. Discussion: The opioid epidemic has exacerbated existing ethical challenges for pain management among youth with SCD. The IEFPM provides a conceptual model that can be integrated into health care settings to facilitate ethical decision-making and promote greater health equity in the clinical management of pediatric sickle cell pain.
Keywords: Adolescent; Analgesics; Anemia; Child; Humans; Opioid; Opioid Epidemic; Pain; Pain Management; Sickle Cell; adolescent; analgesia; child; complication; dept.psy; human; narcotic analgesic agent; pain; peer-reviewed; sickle cell anemia

Morpholino-mediated knockdown of the brain mineralocorticoid receptor affects glucocorticoid signaling and neuroplasticity in wild ocellated wrasse (Symphodus ocellatus) - Nugent, Bridget M.; Stiver, Kelly A.; Han, Jiawei; Kindsvater, Holly K.; Marsh-Rollo, Susan E.; Hofmann, Hans A.; Alonzo, Suzanne H. (BioRxiv, 2021)
Keywords: dept.psy; ⛔ No DOI found

Ejaculate allocation and sperm characteristics differ among alternative male types in a species of fish with cooperation and competition among unrelated males. - Alonzo, Suzanne H.; Stiver, Kelly A.; Kindsvater, Holly K.; Marsh-Rollo, Susan E.; Nugent, Bridget; Kazancıoğlu, Erem (Cells, 2021)
Sexual selection arising from sperm competition has driven the evolution of immense variation in ejaculate allocation and sperm characteristics not only among species, but also among males within a species. One question that has received little attention is how cooperation among males affects these patterns. Here we ask how male alternative reproductive types differ in testes size, ejaculate production, and sperm morphology in the ocellated wrasse, a marine fish in which unrelated males cooperate and compete during reproduction. Nesting males build nests, court females and provide care. Sneaker males only “sneak” spawn, while satellite males sneak, but also help by chasing away sneakers. We found that satellite males have larger absolute testes than either sneakers or nesting males, despite their cooperative role. Nesting males invested relatively less in testes than either sneakers or satellites. Though sneakers produced smaller ejaculates than either satellite or nesting males, we found no difference among male types in either sperm cell concentration or sperm number, implying sneakers may produce less seminal fluid. Sperm tail length did not differ significantly among male types, but sneaker sperm cells had significantly larger heads than either satellite or nesting male sperm, consistent with past research showing sneakers produce slower sperm. Our results highlight that social interactions among males can influence sperm and ejaculate production. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Animals; Fishes; Male; Reproduction; Spermatozoa; Testis; adult; animal; article; controlled study; court; dept.psy; female; fish; human cell; male; metabolism; nesting; nonhuman; peer-reviewed; phenotypic plasticity; reproduction; seminal plasma; sexual selection; social interaction; sperm competition; sperm count; spermatozoon; spermatozoon tail; testis

Positive psychology: Exploring a mindful approach to online learning in higher education - DeLucia, Christine A. (Emerging Realities and the Future of Technology in the Classroom, 2021)
Keywords: dept.psy

The Promise of Automated Home-Cage Monitoring in Improving Translational Utility of Psychiatric Research in Rodents. - Mingrone, Alfred; Kaffman, Ayal; Kaffman, Arie (Frontiers in neuroscience, 2020)
Large number of promising preclinical psychiatric studies in rodents later fail in clinical trials, raising concerns about the efficacy of this approach to generate novel pharmacological interventions. In this mini-review we argue that over-reliance on behavioral tests that are brief and highly sensitive to external factors play a critical role in this failure and propose that automated home-cage monitoring offers several advantages that will increase the translational utility of preclinical psychiatric research in rodents. We describe three of the most commonly used approaches for automated home cage monitoring in rodents [e.g., operant wall systems (OWS), computerized visual systems (CVS), and automatic motion sensors (AMS)] and review several commercially available systems that integrate the different approaches. Specific examples that demonstrate the advantages of automated home-cage monitoring over traditional tests of anxiety, depression, cognition, and addiction-like behaviors are highlighted. We conclude with recommendations on how to further expand this promising line of preclinical research. Copyright © 2020 Mingrone, Kaffman and Kaffman.
Keywords: Actual-HCA; Chora feeder; Intellicage system; PhenoTyper; Review; addiction; anxiety disorder; automated home cage monitoring; automation; behavioral science; cognition; depression; dept.psy; monitoring; nonhuman; peer-reviewed; preclinical study; psychiatry; rodent; rodents; translational research

Audiovisual speech perception in children with autism spectrum disorders: Evidence from visual phonemic restoration. - Irwin, Julia; Avery, Trey; Kleinman, Daniel; Landi, Nicole (Journal of autism and developmental disorders, 2021)
Children with autism spectrum disorders have been reported to be less influenced by a speaker’s face during speech perception than those with typically development. To more closely examine these reported differences, a novel visual phonemic restoration paradigm was used to assess neural signatures (event-related potentials [ERPs]) of audiovisual processing in typically developing children and in children with autism spectrum disorder. Video of a speaker saying the syllable /ba/ was paired with (1) a synthesized /ba/ or (2) a synthesized syllable derived from /ba/ in which auditory cues for the consonant were substantially weakened, thereby sounding more like /a/. The auditory stimuli are easily discriminable; however, in the context of a visual /ba/, the auditory /a/ is typically perceived as /ba/, producing a visual phonemic restoration. Only children with ASD showed a large /ba/-/a/ discrimination response in the presence of a speaker producing /ba/, suggesting reduced influence of visual speech. © 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC part of Springer Nature.
Keywords: Auditory Perception; Autism Spectrum Disorder; Child; Cues; Evoked Potentials; Humans; Speech; Speech Perception; Visual Perception; association; autism; child; dept.psy; evoked response; hearing; human; peer-reviewed; speech; speech perception; vision

The offspring of alcohol-exposed sires exhibit heightened ethanol intake and behavioral alterations in the elevated plus maze. - Koabel, Jennifer; McNivens, Meghan; McKee, Paul; Pautassi, Ricardo; Bordner, Kelly; Nizhnikov, Michael (Alcohol (Fayetteville, N.Y.), 2021)
Research suggests that addictive traits are indeed heritable, but very few preclinical studies have explored transgenerational effects of paternal alcohol exposure. The present study addressed this gap in knowledge. We explored whether offspring of ethanol-exposed sires would be more likely to accept ethanol than descendants of water-exposed and control sires. We also investigated whether the second generation of ethanol-exposed descendants would accept ethanol more than controls and were more or less likely to experience anxiety-like behavior in behavioral assessments. We exposed male rats to repeated binge doses of alcohol (4 g/kg/day across 8 days), water, or left them untreated and mated them with untreated females. We then bred the offspring of these rats to test transgenerational effects of paternal alcohol exposure. We tested 14-day-old offspring from the first and second filial generation for their acceptance of ethanol and water, and measured anxiety-like behavior in 38-day-old, second-generation offspring using an elevated plus maze. The results indicate that offspring of ethanol-exposed sires increase ethanol acceptance in the first generation compared to untreated controls, whereas in the second-generation increased ethanol acceptance vs. these controls is seen in descendants of both ethanol- and vehicle-treated sires. At adolescence, the second generation of rats derived from alcohol-exposed sires exhibited significantly more time spent in the open arms and significantly more arm entries than any other group. The present study suggests that parental ethanol exposure is associated with lingering effects in the infant and adolescent offspring. The second filial generation was also found to be affected, albeit similarly by grandparental ethanol exposure or by the stress of the vehicle administration. Copyright © 2021 Elsevier Inc. All rights reserved.
Keywords: Addictive; Alcohol Drinking; Animals; Anxiety; Article; Behavior; Elevated Plus Maze Test; Ethanol; Male; Maze Learning; Rats; Sprague Dawley rat; addiction; adolescence; adolescent; adult; alcohol; alcohol consumption; animal; animal experiment; animal model; anxiety; behavior disorder; binge drinking; breeding; concentration (parameter); controlled study; dept.psy; drinking behavior; elevated plus maze test; experience; exposure; female; grandparent; inhibitory control; male; maze test; newborn; nonhuman; paternal exposure; peer-reviewed; progeny; rat; sire; vertical transmission; water

Measurement of Motivation States for Physical Activity and Sedentary Behavior: Development and Validation of the CRAVE Scale. - Stults-Kolehmainen, Matthew A; Blacutt, Miguel; Fogelman, Nia; Gilson, Todd A; Stanforth, Philip R; Divin, Amanda L; Bartholomew, John B; Filgueiras, Alberto; McKee, Paul C; Ash, Garrett I; Ciccolo, Joseph T; Brotnow Decker, Line; et al. (Frontiers in psychology, 2021)
Physical activity, and likely the motivation for it, varies throughout the day. The aim of this investigation was to create a short assessment (CRAVE: Cravings for Rest and Volitional Energy Expenditure) to measure motivation states (wants, desires, urges) for physical activity and sedentary behaviors. Five studies were conducted to develop and evaluate the construct validity and reliability of the scale, with 1,035 participants completing the scale a total of 1,697 times. In Study 1, 402 university students completed a questionnaire inquiring about the want or desire to perform behaviors "at the present moment (right now). " Items related to physical activity (e.g., "move my body") and sedentary behaviors (e.g., "do nothing active"). An exploratory structural equation model (ESEM) revealed that 10 items should be retained, loading onto two factors (5 each for Move and Rest). In Study 2, an independent sample (n = 444) confirmed these results and found that Move and Rest desires were associated with stage-of-change for exercise behavior. In Study 3, 127 community-residing participants completed the CRAVE at 6-month intervals over two years- two times each session. Across-session interclass correlations (ICC) for Move (ICC = 0.72-0.95) and Rest (ICC = 0.69-0.88) were higher than when they were measured across 24-months (Move: ICC = 0.53; Rest: ICC = 0.49), indicating wants/desires have state-like qualities. In Study 4, a maximal treadmill test was completed by 21 university students. The CRAVE was completed immediately pre and post. Move desires decreased 26% and Rest increased 74%. Changes in Move and Rest desires were moderately associated with changes in perceived physical fatigue and energy. In Study 5, 41 university students sat quietly during a 50-min lecture. They completed the CRAVE at 3 time points. Move increased 19.6% and Rest decreased 16.7%. Small correlations were detected between move and both perceived energy and tiredness, but not calmness or tension. In conclusion, the CRAVE scale has good psychometric properties. These data also support tenets of the WANT model of motivation states for movement and rest (Stults-Kolehmainen et al., 2020a). Future studies need to explore how desires to move/rest relate to dynamic changes in physical activity and sedentarism. Copyright © 2021 Stults-Kolehmainen, Blacutt, Fogelman, Gilson, Stanforth, Divin, Bartholomew, Filgueiras, McKee, Ash, Ciccolo, Brotnow Decker, Williamson and Sinha.
Keywords: dept.psy; peer-reviewed

Defense against outside competition is linked to cooperation in male-male partnerships - Hellmann, Jennifer K.; Stiver, Kelly A.; Marsh-Rollo, Susan; Alonzo, Suzanne H. (Behavioral Ecology, 2020)
Male–male competition is a well-known driver of reproductive success and sexually selected traits in many species. However, in some species, males work together to court females or defend territories against male competitors. Dominant (nesting) males sire most offspring, but subordinate (satellite) males are better able to obtain fertilizations relative to unpartnered males. Because satellites only gain reproductive success by sneaking, there has been much interest in identifying the mechanisms enforcing satellite cooperation (defense) and reducing satellite sneaking. One such potential mechanism is outside competition: unpartnered satellites can destabilize established male partnerships and may force partnered satellites to restrain from cheating to prevent the dominant male from replacing them with an unpartnered satellite. Here, we manipulated perceived competition in the Mediterranean fish Symphodus ocellatus by presenting an “intruding” satellite male to established nesting and satellite male pairs. Focal satellite aggression to the intruder was higher when focal satellites were less cooperative, suggesting that satellites increase aggression to outside competitors when their social position is less stable. In contrast, nesting male aggression to the intruder satellite increased as spawning activity increased, suggesting that nesting males increase their defense toward outside competitors when their current relationship is productive. We found no evidence of altered spawning activity or nesting/satellite male interactions before and after the presentation. These results collectively suggest that response to outside competition is directly linked to behavioral dynamics between unrelated male partners and may be linked to conflict and cooperation in ways that are similar to group-living species.
Keywords: Satellites; Symphodus ocellatus; alternative reproductive tactics; biological market theory; cooperation; cooperative behavior; defense mechanism; dept.psy; interspecific competition; intraspecific interaction; outside options; peer-reviewed; satellite male; sneak

Big five, linguistic styles, and successful online learning - Abe, J. (Internet and Higher Education, 2020)
With the tremendous growth in online classes and programs at institutions of higher education, conflicting claims are increasingly being made on media and blog sites about the personality types that are compatible with this new learning format. The relations between the Five Factor Model of Personality (FFM) and linguistic styles with measures of academic performance in fully online asynchronous classes were examined. Consistent with findings based on research in face-to-face classes, Conscientiousness, Openness to Experience, and Analytic Thinking were associated with academic success. There was no support for the views propagated on the internet that extraversion, introversion, or anxiety hinder or foster online learning. The most robust predictor of academic performance throughout the semester, independent of the personality variables, was the number of words students contributed to the online discussions. These finding are interpreted within the Community of Inquiry framework (CoI; Garrison, 2003) and future lines of research are suggested. © 2020 Elsevier Inc.
Keywords: Academic performance; Community of Inquiry framework (CoI); Community of inquiry; E-learning; Education computing; Five Factor Model Of Personality (FFM); Five-factor model of personality; LIWC; Linguistic analysis; Linguistics; Online learning; dept.psy; peer-reviewed

Prediction of ethanol self-administration in pre-weanling, adolescent, and young adult rats. - Soledad Fernandez, Macarena; Edward Nizhnikov, Michael; Garcia Virgolini, Rodrigo; Marcos Pautassi, Ricardo (Developmental Psychobiology, 2021)
Alcohol (ethanol) use is almost normative by late adolescence, in most western countries. It is important to identify factors that distinguish those who progress from alcohol initiation to sustained use of the drug, from those that keep a controlled pattern of drinking. The factors precipitating this transition may change across development. This study analyzed associations between behavioral endophenotypes and ethanol intake at three developmental periods. Exp. 1 measured ethanol drinking at postnatal day 18, via an intraoral infusion procedure, in male or female pre-weanling rats screened for anxiety response in the light-dark box test and for distance traveled in a novel open field. Exp. 2 measured, in juvenile/adolescent or young adult rats, the association between shelter seeking, exploratory/risk-taking behaviors, anxiety or hedonic responses, and ethanol intake. Ethanol intake in pre-weanlings was explained by distance traveled in a novel environment, whereas anxiety responses, measured in the multivariate concentric square field apparatus (MSCF), selectively predicted ethanol intake at adolescence, but not at adulthood. Those juvenile/adolescents with lower mean duration of visit to areas of the MSCF that evoke anxiogenic responses exhibited heightened ethanol intake. These findings suggest that the association between anxiety and ethanol intake may be specifically relevant during adolescence. © 2020 Wiley Periodicals LLC
Keywords: Alcohol Drinking; Animals; Anxiety; Ethanol; Female; Male; Rats; Self Administration; Wistar; Wistar rat; adolescents; alcohol; animal; anxiety; dept.psy; drinking behavior; drug self administration; ethanol intake; female; male; peer-reviewed; pre-weanling rat; rat

N400 amplitude, latency, and variability reflect temporal integration of beat gesture and pitch accent during language processing. - Morett, Laura M; Landi, Nicole; Irwin, Julia; McPartland, James C (Brain Research, 2020)
This study examines how across-trial (average) and trial-by-trial (variability in) amplitude and latency of the N400 event-related potential (ERP) reflect temporal integration of pitch accent and beat gesture. Thirty native English speakers viewed videos of a talker producing sentences with beat gesture co-occurring with a pitch accented focus word (synchronous), beat gesture co-occurring with the onset of a subsequent non-focused word (asynchronous), or the absence of beat gesture (no beat). Across trials, increased amplitude and earlier latency were observed when beat gesture was temporally asynchronous with pitch accenting than when it was temporally synchronous with pitch accenting or absent. Moreover, temporal asynchrony of beat gesture relative to pitch accent increased trial-by-trial variability of N400 amplitude and latency and influenced the relationship between across-trial and trial-by-trial N400 latency. These results indicate that across-trial and trial-by-trial amplitude and latency of the N400 ERP reflect temporal integration of beat gesture and pitch accent during language comprehension, supporting extension of the integrated systems hypothesis of gesture-speech processing and neural noise theories to focus processing in typical adult populations. Copyright © 2020 Elsevier B.V. All rights reserved.
Keywords: Adolescent; Adult; Beat gesture; Brain; Electroencephalography; Evoked Potentials; Evoked response variability; Female; Humans; Language; Male; N400; Pitch Perception; Pitch accent; Speech; Speech Perception; Temporal integration; Young Adult; adolescent; adult; article; brain; comprehension; controlled study; dept.psy; electroencephalography; event related potential; evoked response; female; gesture; human; human experiment; language; language processing; male; noise; peer-reviewed; physiology; pitch; pitch perception; speech; speech perception; videorecording; young adult

Motivation States for Physical Activity and Sedentary Behavior: Desire, Urge, Wanting, and Craving. - Stults-Kolehmainen, Matthew A; Blacutt, Miguel; Bartholomew, John B; Gilson, Todd A; Ash, Garrett I; McKee, Paul C; Sinha, Rajita (Frontiers in psychology, 2020)
To better explain daily fluctuations in physical activity and sedentary behavior, investigations of motivation are turning from social cognitive frameworks to those centered on affect, emotion and automaticity, such as the Affect and Health Behavior Framework (AHBF), Integrated Framework and Affective-Reflective Theory (ART). This shift has necessitated: (a) re-examination of older theories and their constructs, such as drives, needs and tensions and (b) an inspection of competing theories from other fields that also attempt to explain dynamic changes in health behaviors. The Dynamical Model of Desire, Elaborated Intrusion Theory and others commonly share with AHBF the idea that human behavior is driven strongly by desires and/or the similar concepts of wants, urges, and cravings. These affectively-charged motivation states (ACMS) change quickly and may better explain physical activity behavior from one moment to the next. Desires for movement predominantly derive from negative but also positive reinforcement. Data from clinical populations with movement dysfunction or psychiatric disorders provides further evidence of these drivers of movement. Those with Restless Legs Syndrome, akathisia, tic disorders and exercise dependence all report strong urges to move and relief when it is accomplished. Motor control research has identified centers of the brain responsible for wants and urges for muscular movement. Models elaborated herein differentiate between wants, desires, urges and cravings. The WANT model (Wants and Aversions for Neuromuscular Tasks) conceptualizes desires for movement and rest as varying by magnitude, approach or avoidance-orientation (wants versus aversions) and as occupying independent dimensions instead of opposite ends of the same axis. For instance, one hypothetically might be in a state of both high desire for movement and rest simultaneously. Variations in motivation states to move and rest may also be associated with various stress states, like freezing or fight and flight. The first validated instrument to measure feelings of desire/want for movement and rest, the CRAVE Scale (Cravings for Rest and Volitional Energy Expenditure) is already shedding light on the nature of these states. With these advances in theory, conceptual modeling and instrumentation, future investigations may explore the effects of desires and urges for movement and sedentary behavior in earnest. Copyright © 2020 Stults-Kolehmainen, Blacutt, Bartholomew, Gilson, Ash, McKee and Sinha.
Keywords: conceptual analysis; dept.psy; desire; exercise; motivation; motivation states; peer-reviewed; physical activity; sedentary activity; urge for movement

College student sleep and executive functioning: An examination of potential moderators - Cifre, Anthony B.; Walters, Kenneth S.; Budnick, Christopher J. (Translational Issues in Psychological Science, 2020)
Approximately 60% of college students report sleep disturbances. Sleep disturbances, such as insomnia, negatively influence physical energy, cognitive resources, and affective states that might inhibit executive functioning. To better delineate the variables that alter the college student insomnia and executive functioning relationship we examined sleepiness, sleep debt, and attention-deficit/hyperactivity disorder (ADHD) symptomatology. We expected insomnia to predict executive dysfunction, with a stronger relationship observed at higher levels of the focal moderator (i.e., sleepiness, sleep debt, or ADHD symptoms). Undergraduate participants (n = 472) completed a cross-sectional survey assessing insomnia, state sleepiness, sleep debt, ADHD symptomatology (inattention, hyperactivity, and impulsivity), and executive dysfunction. Hierarchical linear regressions showed that poor sleep had a negative influence on executive function when college students also had high levels of impulsivity, state sleepiness, or sleep debt. These results partially support our expectations and further the academic sleep-related literature while providing insight for counselors, academic advisors, or other professionals working with college student populations. (PsycInfo Database Record (c) 2020 APA, all rights reserved)
Keywords: Attention Deficit Disorder with Hyperactivity; College Students; Executive Function; Financial Strain; Insomnia; Sleep; Sleepiness; Symptoms; dept.psy; peer-reviewed

Impact of enriched environment during adolescence on adult social behavior, hippocampal synaptic density and dopamine D2 receptor expression in rats - Gabriel, Paul; Mastracchio, Toni-Ann; Bordner, Kelly; Jeffrey, Rachel (Physiology & Behavior, 2020)
Environmental enrichment (EE) is one experimental manipulation that induces changes in the brain. However, it is important to distinguish between physical and social components of enrichment. To this end we established four groups of rats reared in different enriched environments during the adolescent period. Our results indicate heightened social memory and increased spine density in dentate gyrus specifically in socially enriched animals. Physical enrichment increased spine density in CA1. Dopamine D2 receptor expression in hippocampus was decreased across all enrichment conditions. Altogether, our results demonstrate differing effects of physical and social enrichment, supporting an important role for environment in synaptogenesis, behavior, and dopaminergic signaling. © 2020 The Authors
Keywords: Adolescence; Animals; Article; Dopamine; Environment; Environmental enrichment; Hippocampus; Memory; Rats; Receptors, Dopamine D2; Social Behavior; Social enrichment; Synapse density; animal; animal behavior; animal experiment; controlled study; dentate gyrus; dept.bio; dept.psy; dopamine 2 receptor; dopaminergic transmission; environment; environmental enrichment; female; hippocampal CA1 region; hippocampus; male; memory; nonhuman; peer-reviewed; priority journal; protein expression; rat; social behavior; spine; synapse; synaptogenesis

A preliminary investigation into collegiate student-athletes’ attitudes towards athletic trainers and sport psychology consultants - Ildefonso, Kenneth; Blanton, Jedediah; Durwin, Cheryl; Arvinen-Barrow, Monna; Kamphoff, Cindra (Journal of Sport, 2020)
To investigate if athletes’ attitudes toward athletic trainers and sport psychology consultants differ considering nature of athletic ability beliefs and previous experiences with these professionals; collegiate student-athletes (n = 114 male, n = 81 female, M age = 19.77, SD = 1.43) completed the Conceptions of the Nature of Athletic Ability Questionnaire-2 (Biddle, Wang, Chatzisarantis, & Spray, 2003), Attitudes Toward Athletic Trainers-Form (modified from the Attitudes toward Physiotherapist-Form; Arvinen-Barrow, Clement, & Bayes, 2012), and the Sport Psychology Attitudes Revised-Form (Martin, Kellman, Lavallee, & Page, 2002). Multiple analyses of variance revealed small statistically significant mean differences in attitudes considering ability beliefs, previous athletic training, and sport psychology experiences. Athletes with previous athletic training experience were less confident in their athletic trainer than those without such experience. In contrast, athletes with previous sport psychology experience were more confident in their consultant than those without such experiences. Results suggest athletes’ attitudes towards helping professionals may be partially influenced by subjective norms and expectations about the nature of such relationships.
Keywords: dept.psy; peer-reviewed

Child and Adolescent Development: A Social Justice Approach - Anthis, Kristine (Cognella, 2021)
Child and Adolescent Development: A Social Justice Approach features portraits of development at each stage interwoven with the findings of developmental science research on how inequitable resources and opportunities, which are influenced by social, economic, and political factors, can impact development. The text also presents findings on how such data can be used to reduce inequities for children and their families, thereby optimizing development and allowing individuals to reach their full potential no matter who they are. The text begins with a chapter that briefly describes the stages, domains, and patterns of child and adolescent development, as well as traditional and contemporary theories. Subsequent chapters provide insight into the research methods of developmental science and explain how epigenetic influences affect development. The book then progresses chronologically, discussing the physical, cognitive, and emotional changes that occur within each stage, guiding readers through a tapestry of development from conception through adolescence. Throughout, Pan & Zoom sections supply both big-picture and microscopic understandings of development, Tech & Media asides highlight the influences that technology and media can have on child and adolescent development, and Mentor Minutes provide readers with practical wisdom through interviews with diverse professionals working in the field. Featuring a timely and much-needed perspective on development, Child and Adolescent Development is an ideal resource for courses in psychology, education, counseling, human services, and social work.
Keywords: Child development; Youth development; SCSU Faculty Scholar Award; award_winner; dept.psy

The fear of missing out at work: Examining costs and benefits to employee health and motivation - Budnick, Christopher J.; Rogers, Arielle P.; Barber, Larissa K. (Computers in Human Behavior, 2020)
The popular business media argues that the “fear of missing out” (FoMO) on work-related opportunities harms employees’ health and performance. Yet, these claims rely on the study of FoMO in college students in non-work contexts. Therefore, we explored workplace FoMO among employees across three studies. We first developed a measure and provided validation evidence for workplace FoMO among diverse employees (N = 324; Study 1) and MBA students (N = 223; Study 2). Using a third large employee sample (N = 300; Study 3), we tested whether workplace FoMO predicted health (i.e., work burnout and work well-being) and motivational outcomes (i.e., message-checking behaviors and work engagement). We also examined whether family-supportive organizational perceptions (FSOP) moderated these relationships. Results indicated that workplace FoMO is a distinct construct from other measures, including general FoMO. Workplace FoMO also predicted work burnout and message checking behavior, but not work well-being. Lower levels of FSOP strengthened the positive relationship between workplace FoMO and message checking behavior, but also produced a positive relationship between workplace FoMO and work well-being. Overall, FoMO appears to be relevant to the work context and predicts both employee well-being and behavior outcomes. © 2019 Elsevier Ltd
Keywords: Behavioral research; College students; Costs and benefits; Employee health; Fear of missing out; Health; Job satisfaction; Motivation; Students; Technology use; Technology use at work; Well being; Work engagements; Work-related; article; burnout; controlled study; dept.psy; fear of missing out; human; major clinical study; motivation; peer-reviewed; perception; wellbeing; work engagement